التربية الخاطئة له دور كبير في شكل موقف العنف - Wawan Djunaedi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
Commitment to say no to violance probably is consensus among people on the world. No one want to see blood-shed, butchering to women, chindren, and weak group (read: mustadh’afin). The Glorious hope of human actually is in line with all religion creeds. Neither religion nor sect of faith spread teachings except the values of peacefulness and anti violance. Budha teachs unpretentiousness, Christian gives lessons to somebody about love and pity, Confusius makes its followers practice wisdom, Islam advices Moslem to spread mercy for all of the world. However, religion which has the glorious values often appear to be evil face. Many good teaching in some religions were misinterpreted and in fact made as legitimation tools for extreme actions via distortive religious education. This article will focus on discussion about how is the relation between religious educational values and extreme actions among religion followers reflected ambiguous, inconsistent, and contradictive relation.